COMPULSORY MOTOR INSURANCE IN UZBEKISTAN AS AN INSTITUTION OF SOCIAL COMPENSATION AND FINANCIAL DISCIPLINE - Abdujabborov , Islomiddin (Zamonaviy ilmiy yondashuvlar va texnologik taraqqiyotning ustuvor yo‘nalishlari, 2026)
This thesis analyzes the system of compulsory motor third-party liability insurance in Uzbekistan as an institution that ensures social compensation, financial discipline, and the mass development of the insurance market. While previous studies have mainly evaluated compulsory motor insurance from the perspective of market size, premiums, and payout dynamics, this thesis interprets its primary function as transforming damages caused by road traffic accidents from personal disputes or informal settlements into a regulated financial compensation mechanism. According to official data, in 2025, insurance premiums for motor third-party liability amounted to 406.165 billion UZS, insurance payouts reached 245.224 billion UZS, and the number of active contracts totaled 6,221,221. These figures demonstrate that this type of insurance is not only a mandatory segment but also an essential component of a broader financial protection system. The thesis concludes by identifying key priorities for expanding compulsory motor insurance, including digital monitoring, transparency of payments, risk-based tariff setting, and the promotion of insurance culture.